Mombolasuako Perspektif Istihsan Studi di Kecamatan Loea Kabupaten Kolaka Timur - Elen, Elen (KALOSARA: Family Law Review, 2024)
Girls are required to introduce and ask their parents' permission before choosing a life partner, but if they do not get permission from their family, then the child will elope. This research is a field study that uses descriptive qualitatif and the data collestion technige uses theree methods namely Observation, interviews and documentation. Based on the research findings, there are several variables that cause couples to elope (mombolasuko) in Loea District, East Kolaka Regency, including: (1) the girl's parents do not approve; and (2) a large dowry. The situation of couples who elope is still considered one of a stable household, and the procedure for ending elopement (mombolasuako) is divided into three stages: 1) the stage of delivering the news (molamba obiri or mowoka obiri); 2) the stage of membentenggi (mesokei); and 3) the stage of handing over the main custom (mowindahako). In this Istihsan perspective, remarriage is the process of ending elopement. They look for a good one by going through the customary stages, and even then they must get approval from the woman's parents, the tolea or customary leader, and the man.